A multidisciplinary approach of impacted and transposed maxillary canine: A case report - Dimas Iman; Ida B Narmada; Muchammad R Yusuf; Ratna Putri (Wolters Kluwer Medknow Publications, 2023)
The impacted and transposed teeth cause consequences in tooth eruption and movement, resulting in aesthetic and functional outcomes. A proper treatment plan with treatment duration and cost consideration is necessary to treat them. This study reported treatment for a 23-year-old male patient with impacted and transposed canine in maxilla using a multidisciplinary method between orthodontic and conservation. According to the anamnesis of the patient, his upper arch midline contained an extra tooth when he was a child. With the consideration of the duration and cost of treatment, the preferable and manageable treatment fell into the correction using a fixed orthodontic appliance with careful mechanics and enameloplasty to achieve the aesthetic and functional goal.